2017
DOI: 10.1002/cssc.201700271
|View full text |Cite
|
Sign up to set email alerts
|

Poly(4‐Vinylpyridine)‐Based Interfacial Passivation to Enhance Voltage and Moisture Stability of Lead Halide Perovskite Solar Cells

Abstract: It is well known that the surface trap states and electronic disorders in the solution-processed CH NH PbI perovskite film affect the solar cell performance significantly and moisture sensitivity of photoactive perovskite material limits its practical applications. Herein, we show the surface modification of a perovskite film with a solution-processable hydrophobic polymer (poly(4-vinylpyridine), PVP), which passivates the undercoordinated lead (Pb) atoms (on the surface of perovskite) by its pyridine Lewis ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
132
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 48 publications
1
132
0
Order By: Relevance
“…Primarily, there are two factors that govern the uniformity of PbI 2 layer: crystallization process and proper dissolution of PbI 2 into the main solvent . In sequential deposition of perovskite, dimethylformamide (DMF) is used as a solvent to dissolve PbI 2 ; however, the presence of the non‐negligible amount of water in the PbI 2 leads to its improper solubility in precursor solution at the molecular level . This can directly impact the crystallization process and, consequently, give rise to non‐uniform PbI 2 layer with a large number of pinholes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, there are two factors that govern the uniformity of PbI 2 layer: crystallization process and proper dissolution of PbI 2 into the main solvent . In sequential deposition of perovskite, dimethylformamide (DMF) is used as a solvent to dissolve PbI 2 ; however, the presence of the non‐negligible amount of water in the PbI 2 leads to its improper solubility in precursor solution at the molecular level . This can directly impact the crystallization process and, consequently, give rise to non‐uniform PbI 2 layer with a large number of pinholes .…”
Section: Resultsmentioning
confidence: 99%
“…THF additive‐based non‐encapsulated perovskite devices showed enhance stability when exposed to the ambient atmosphere (relative humidity of ≈50%) compared with non‐additive based devices when stored under the same condition. It is reported that perovskite layer with defect states tends to degrade rapidly which can be the reason for rapid degradation in the device performance in the non‐additive case, whereas the enhanced stability in THF additive case can be credited to the formation of compact perovskite layer, enhanced crystallinity, and reduced defect states. The obtained result indicates that in mesoporous architecture, obtaining smooth and pinhole‐free PbI 2 layer is critically important to obtain a perovskite layer with fewer defects and voids.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that poly(ethylene glycol) as a self‐healing scaffold for CH 3 NH 3 PbI 3 perovskite formation improved the cell durability. The residual polymers or polymer coating upon the perovskite layer have also been frequently reported to form a hydrophobic thin layer to give water repellency on the formed layers . However, conventional polymers are electrically insulating and the addition of a certain amount of polymers inside of and/or upon the perovskite layers usually reduced the photovoltaic performance of the cells, especially the current density.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Grätzela nd co-workers [35] reported that a small addition of poly(methyl methacrylate) (PMMA) in ap erovskite formatione nhanced the perovskite grain quality and yielded ah igherc onversion efficiency,a nd Zhao et al [36] demonstrated that poly(ethylene glycol) as as elf-healing scaffold for CH 3 NH 3 PbI 3 perovskite formation improved the cell durability.T he residual polymers or polymer coating upon the perovskite layer have also been frequently reported to form ah ydrophobic thin layer to give water repellency on the formed layers. [37] However,c onventional polymers are electrically insu-As mall amount of ar adical-bearing redox-active polymer, poly(1-oxy-2,2,6,6-tetramethylpiperidin-4-ylm ethacrylate) (PTMA), incorporated into the photovoltaic organo-lead halide perovskite layer significantly enhanced durability of both the perovskite layer andi ts solar cell and even exposure to ambient air or oxygen.P TMA acted as an eliminating agent of the superoxide anion radicalf ormed upon light irradiation on the layer,w hichc an react with the perovskite compound and decompose it to lead halide.Acell fabricated with aP TMA-incor-poratedp erovskite layer and ah ole-transporting polytriarylamine layer gave ap hotovoltaic conversion efficiency of 18.8 % (18.2 %f or the control without PTMA). The photovoltaic current was not reduced in the presence of PTMA in the perovskite layer probably owing to ac arrier conductivity of PTMA.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Poor device performance arising from charget rapping at interfaces [20] have fueled investigation into non-radiativel oss reductions, which include incorporation of excessp recursorm aterial in the perovskite solution, [21] solvent engineering processes [22] and even through layering of passivating materials to inhibit moisture and oxygen permeation. [18,23] However,t hese methodsh ave only shown limited success.T he introduction of excess precursor material resulted in higherh ysteresis duet ot he increased effect of ionic migration under device operation [24,25] whereas too thick ap assivation layer can have adverse effect on device performance ensuing from reduced carrier injection efficacy. [26,27] Herein, it is shown that by incorporating aq uaternary ammoniumc ompound-tetraethylammonium bromide (TEABr)into methylammonium lead bromide (MAPbBr 3 )t hrough a facile postdeposition step, grain size modulation and passivation of surfaced efects;a se videncedb yt he increased photolu-Metal halide perovskites have demonstrated breakthrough performances as absorber and emitter materials for photovoltaic and display applications respectively.H owever,d espite the low manufacturing cost associated with solution-based processing, the propensity for defect formation with this technique has led to an increasing need for defect passivation.…”
Section: Introductionmentioning
confidence: 99%